Engineering Transfer Students' Reasons for Starting at Another Institution and Variation Across Subpopulations. (January 2020) - Ogilvie, Andrea M.; Knight, David B.
Bolstering transfer pathways to a 4-year degree can help fill the country's increasing need for innovative, diverse, skilled workers within engineering. Drawing on survey data from a sample comprised of a disproportionately large percentage of Hispanic/Latino students, this study focuses on understanding engineering transfer students' reasons for starting at a different institution. Financial/Affordability, Nonacademic Commitments, and Academic Flexibility were top reasons for starting at a different institution with multiple differences across subpopulations like Hispanic/Latino status.